Improving the efficiency of budget for the provision of social sevices rendered (Путеводитель предпринимателя, 2020)
The article analyzes the nature and fundamental ways to improve the planning of budget spending on state and municipal social services to the public, are considered the problems and methods to improve the efficiency of budget expenditures on social development.